Analysis Variations of Riser in Sand Casting for Scrap Aluminum on Hardness Values - Zainal Abadi; Andre Kurniawan; Andril Arafat; Nur Ichsan Abdillah; Daffa Raihan Senthot (Universitas Negeri Padang, 2021)
Abstract In this study, we will discuss the process of casting used aluminum metal. Used aluminum is one of the industrial wastes that can be converted into products using the casting method. This study aims to obtain a good casting material with good hardness values ​​and minimal defects. The research will focus on the results of castings by analyzing the visuals and hardness values ​​of the specimens. The research design is a pre-experimental type of One-Shot Case Study by conducting treatments whose results will be directly observed and analyzed descriptively. The treatment given is to increase the number of risers in recycled aluminum castings. Variations in the number of risers are 1 riser, 2 riser, and 3 riser. Each variation has 3 specimens, so there are 9 specimens in the study. The data from the test results contained a fairly large porosity value for each riser variation. The hardness value that has been tested using the Rockwell hardness tester obtained the highest hardness value occurs in the 2 riser variation, namely 27.69 HRA and the lowest hardness value occurs in the 3 riser variation, namely 21.56 HRA. Thus, for casting used aluminum with a casting pattern as in this study, it is best to use 2 risers.